Tolerance and Intolerance in the Croatian-Slavonian Kingdom at the Turn of the 17th Century. Contest for Gomirje - Štefanec, Nataša (2007)
Article presented results of a micro-historical research of one case study indicative for a large part of the Croatian-Slavonian Kingdom in the 16th and the first half of the 17th century. It examined patterns of behaviour of various 'actors' included into the contest over Gomirje (earliest local population, assimilated settlers, newly arriving Vlachs, Croatian-Slavonian noblemen, Austrian military authorities, the Croatian-Slavonian Diet, the Catholic Church and the king). Attempting to resettle desolated territory under their own terms and to accomplish diverse goals, all included 'actors' exhibited variously motivated patterns of intolerant and tolerant behaviour. The main reasons of intolerant patterns of behaviour were legal status, economic advancement and military considerations - depending on the faction. On the very frontier of Islam and Christianity (fiercely divided Christianity!) religion was not among the main triggers of intolerant behaviour. The religious 'reconciliation' in the period and area considered resulted from interest-oriented intolerance.
ENG